2014
DOI: 10.5007/1980-0037.2014v16n5p522
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos do exercício de força versus combinado sobre a hipotensão pós-exercício em mulheres com síndrome metabólica

Abstract: Effects of resistance exercise versus combined training on post-exercise hypotension in women with metabolic syndrome Efeitos do exercício de força versus combinado sobre a hipotensão pós-exercício em mulheres com síndrome metabólicaAbstract -The aim of the present study was to analyze the response of systolic (SBP) and diastolic (DBP) blood following three experimental sessions: resistance exercise (RE), combined exercise (COMB-aerobic and RE) and control session (CON). Thirty women with metabolic syndrome (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Similarly, the concurrent training-induced longer duration and magnitude of PEH in comparison to strength training. Tibana et al 11 also reinforces that findings in a sample composed of women with metabolic syndrome.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Similarly, the concurrent training-induced longer duration and magnitude of PEH in comparison to strength training. Tibana et al 11 also reinforces that findings in a sample composed of women with metabolic syndrome.…”
Section: Discussionsupporting
confidence: 62%
“…The duration of PEH was longer after concurrent training in comparison to other training models [27][28][29] . Greater magnitude PEH was observed for aerobic training compared to concurrent training 27 and for concurrent training in comparison to strength training 11 . Saccomani et al 22 found higher and longer PEH for concurrent training compared to aerobic and strength training.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…The effectiveness of concurrent training in the prevention and treatment of cardiovascular problems has mainly been observed in the elderly (Ferrari et al, 2016;Tibana et al, 2014); where the low adherence of this population to systematic training may be related to a low response to exercise programs (Segundo et al, 2016). To increase adherence, some researchers have proposed the use of self-selected intensity for the prescription of resistance and aerobic training programs that are performed alone (Aoike et al, 2012;Glass, 2008).…”
Section: Introductionmentioning
confidence: 99%